PENGGUNAAN MEDIA SOSIAL TIKTOK SEBAGAI PENGEMBANGAN EKSISTENSI DIRI: (STUDI KASUS PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK ANGKATAN 2019 UNIVERSITAS SLAMET RIYADI SURAKARTA) - Khasanah, Isnaini Lailatul; Sekar Wangi, Maya; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Existence has an important role in expressing oneself, especially through social media such as TikTok. TikTok's popularity is growing and is of interest to young people, especially students. The informants in this study were selected using purposive sampling, as many as 3 students from the Faculty of Social and Political Sciences from Slamet Riyadi University, Surakarta with the TikTok user account names @fajri.i, @wulanmudmud.hehe and @lauraanste who used TikTok social media to display creativity through creating videos or content to gain popularity. Method used is a qualitative method which aims to explain an in-depth phenomenon by collecting data related to the research. Data collection techniques in this research are by observation, interviews and documentation. In this research, Erving Goffman's Dramaturgical Theory is used, a theory that describes life as a drama performance with two aspects of self-image, namely, front stage and back stage. The results of this research are the use of TikTok to develop self-existence in the front stage aspect of the three student accounts @fajri.i, namely comedian, @wulanmudmudhehe, namely influencer and @lauraanste, namely beauty creator. Meanwhile, in the back stage aspect, things are not visible on the front stage and prepare various strategies to prepare for the front stage. KEYWORDS: Existence, TikTok and Dramaturgical